Мовчання як екстралінгвальний компонент у драматичному тексті буковинських письменників - Ivanna, Struk (Чернівці–Сучава: БДМУ, 2020)
The research is devoted to the interaction of verbal and non-verbal means of communication in the dramatic text. In the scientific research, the expansion of the semantic space of terms is taken into account. It helped to understand the theory and enabled to use the idea of communication. Taking into account the specificity of dramatic text (DT) – it’s clearly distinguished author's speech and speech of characters. DT is defined as a two-level entity, which is the unity of verbal2 (character speech) and non-verbal communication (author’s communication); a complex semiotic unit, the polyphony of which forms author's speech. Scientific novelty. Introduced to the terminology apparatus of the DT the notion of implication, which is understood by the minimal structural and semantic unity of verbal and non-verbal components (remarks and replicas) that are viewed as single visual, cognitive and communicative, provide a comprehensive pragmatic influence on the addressee. Taking into account a) the achievements of the theory of verbal and non-verbal communication, b) the priority of the author's speech in DT, c) the theatrical realization of the dramatic action, the classification of the implications is proposed: 1) implicators on the basis of the main remarks; 2) implicators for speech tracks; 3) implications for introductory remarks with a zero verbal component. The implicatiure of the speech tracks in the DT, which are represented by the extralinguistic components of communication, are described. The purpose of the article is to analyze extralinguistic implicatures with remarks on the designation of silence and their linguistic means in the dramatic texts of Bukovinian writers (Yu. Fedkovich, S. Vorobkevich, S. Yarychevsky, I. Sinyuk). Communicatively meaningful silence has a certain emotional color and is a means of communication that gives a variety of communicative meanings of a semantically-pragmatic nature. The following methods and techniques of linguistic analysis are used to achieve the goal and task: the system-functional analysis, the method of discursive analysis, the contextual-interpretive method, the method of stylistic analysis, the conversion analysis. The prospect of the study involves a systematic analysis of the implications, taking into account the universal, ethnospecific and individual markers of the dramatic text of the Bukovinian writers.
Silence as an extralingual component in the dramatic text of Bukovinian writers
Keywords: dramatic text, remark, implicature, extralingual means of communication, silence